Relationship Between Negative Events and Depression Among Taekwondo Students in Mazandaran University's - Roghayeh Gholampour Goli; Mohammadbagher Forghani Ozrudi; Somayeh Faghanpour (Selcuk University, 2021)
The aim of this Research was to examine relationship between negative events and depression among Iranian Taekwondo students. This research was conducted on the appropriate sample of 116 Taekwondo students from Mazandaran university, being 18-24 years old. The applied measure instruments were - Adolescent Perceived Events Scale, Automatic Thoughts Questionnaire, General Self-Efficacy Scale, Confrontation with Stressing Situation Questionnaire, Social Support Questionnaire, Children's Depression Rating Scale-demonstrated satisfactory reliability. The data was processed using descriptive parameters, Pearson's correlation coefficient and hierarchy regression analysis amp; SPSS22 software. Achieved results didn't show that predictor variables (common automatic thoughts, the sense of general self-efficiency, confrontation strategies and perceived support of family, coach and team peers) are the cause of the common negative events and depression relations of Taekwondo students in the middle period of adolescence. On contrary, the results have emphasized the fact that mutual relations of common negative events and depression of Taekwondo students, in this young category, can be explained using independent variables (unwilling unconscious negative thoughts, confrontation focused on feelings, as well as support of family, coach and team peers).